Techniques d'abréviation dans les webchats francophones - Krautgartner, Klara (Linguistik Online, 2003)
lut toi, asv stp? - In a French speaking webchat you can find a good deal of messages like these which are quite normal for the regular chatter, but often incomprehensible for the non specialist (the example above means 'salut toi, âge, sexe, ville s'il te plaît'). Chat communication is characterised by an extreme rapidity. The more users participate, the faster turns disappear from the screen. So the chatters better create very short messages.This paper intends to study different types of abbreviation through real time written interactions in French speaking webchats. How do users shorten their messages? How do they succeed in communicating a maximum of content using the least possible number of (ASCII-) signs? On the base of examples and statistic data the paper presents conventional types of abbreviation such as h instead of heure, acronyms, apocopes etc. as well as more innovative abbreviation strategies as for instance phonetic writing (c for c'est) or words reduced to their consonants (e.g. ms instead of mais). All these strategies constitute an essential linguistic tool in chat writing.